COMPARING ILLNESS PERCEPTIONS BETWEEN OLDER ADULTS WITH TYPE 2 DIABETES AND THOSE WITH MILD COGNITIVE IMPAIRMENT. (16th November 2018) - Kim, H; Lingler, J; Bender, C; Albert, S; Sereika, S
Abstract: The burden of chronic disorders impacting physical and mental health in late-life suggests the need to understand individuals' illness perceptions (IPs), taking into account disease characteristics (DC) (physical vs. mental disorders). We compared IPs between persons experiencing type 2 diabetes (T2DM) and mild cognitive impairment (MCI) as exemplars of common late-life physical and mental disorders. This cross-sectional study of persons with T2DM (PwT2DM; n=146) and persons with MCI (PwMCI; n=81) used existing baseline data from the Brief Illness Perception Questionnaire pooled from two clinical trials. Hierarchical linear regression was used to examine main effects for DC (T2DM vs. MCI), potential covariates, and interactions between DC and covariates. Compared to PwMCI, PwT2DM viewed T2DM as more chronic (p=.022) but within their personal (p=.042) and treatment (p<.001) control. PwT2DM had a higher-perceived understanding (p=.001) and endorsement of being upset (p<.001) compared to PwMCI. Yet, PwMCI experienced more symptoms (p=.023) and had more concerns about their condition compared to PwT2DM (p<.001). Interactions were also found indicating having MCI and more comorbid conditions were associated with lower perceptions of the seriousness of consequences (p=.028), symptom identity (p=.035), and concerns (p=.013) regarding MCI. Having MCI and lower levels of education were associated with higher perceptions of the MCI's controllability by treatments (p=.011), while having MCI and older age was related to a better-perceived illness understanding of MCI (p=.018). Findings suggest that older adults may view mental disorders differently than physical disorders, which may have implications for patient education and interventions to facilitate symptom management.